Bi Doped TiO2 as a Photocatalyst for Enhanced Photocatalytic Activity - İlknur Altın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study is based on the preparation of TiO2 and bismuth doped TiO2 (Bi-TiO2) nanoparticles by surfactant-assisted sol-gel approach. The physiochemical characteristics of prepared samples were examined by X-ray diffraction technique (XRD), Fiel emission scanning electron microscopy-energy dispersive analysis (FESEM-EDS), and UV-visible diffuse reflectance spectroscopy (UV-vis DRS). The XRD patterns revealed that the anatase crystal phase was only formed with high crystallinity. The band gap energies were measured to be of 3.11 eV for TiO2-2 and 3.02 eV for Bi-TiO2 by ultraviolet (UV)-visible diffuse reflectance spectroscopy, revealing that doping Bi improves the efficient interactive relation of the catalyst with visible light. Also, EDS results confirm that Bi particles are immobilized on the surface of TiO2 successfully. The activities of the catalysts were tested by photocatalytic degradation of methylene blue (MB) under the visible light. Bi-TiO2 photocatalyst could achieve the best MB degradation percentage of 70.2% after 180 min. of visible irradiation. Additionally, effect of some experimental parameters such as effect of humic acid (HA) and pH has been evaluated as much as reusability of catalyst. The characterization results confirmed the successful and desired preparation of the catalysts. The Bi-TiO2 presented significant visible light response photocatalytic activity for the degradation of MB.